Evaluation of Presignals at Oversaturated Signalized Intersections. Issue 1 (January 2014) - Guler, S. Ilgin; Menendez, Monica
One of the major causes of bus delays in urban environments is signalized intersections. A commonly used solution to give priority to buses at signalized intersections is to dedicate a lane for bus use only. This strategy allows the bus to skip the car queues and minimizes the bus delay experienced at the signal. However, especially for low bus flows, the strategy can waste valuable green time at signals and impose additional car delays. Overall, even when bus passengers enjoy reduced travel times, the total person hours of delay in the system can increase. To avoid this problem and utilize the full capacity of the main signal while still providing bus priority, the use of a presignal has been proposed. The goal of this research was to quantify the benefits of the use of presignals in system wide total person hours of delay, specifically for oversaturated intersections. Theoretical formulas were developed to quantify the effects of a presignal on traffic flow, and the formulas were empirically verified. The theoretical model was used to compare the total delay with a presignal strategy with the total delay with a dedicated bus lane or fully mixed lanes. Bounds on bus-to-car occupancy ratios were quantified for which presignals provided the lowest delay compared with a dedicated lane or mixed lane strategy. The results showed that for oversaturated intersections, presignals were better for the system than dedicated bus lanes. Moreover, presignals could decrease the total person hours of delay compared with mixed lanes for large car demands.